Kovid Gara (Comic Video Ragam Nusantara) as a Digital Learning Innovation Based on Local Culture to Increase Cultural Love and Character in Golden Age Children - Purmayanti, Ni Putu (JPKMI (Jurnal Pengabdian Kepada Masyarakat Indonesia), 2024)
Since the pandemic, the use of gadgets for early childhood has become more prevalent and can have both good and bad effects. One of the dangerous things for children is the number of features or applications that are not suitable for children's age, poor norms, and not educational. Therefore, KOVID GARA (Komik Video Ragam Nusantara) is here to help parents and teachers of golden age children in providing the right content for children. The purpose of KOVID GARA is to provide linguistic and cultural education presented in the form of cartoon shows that can attract children's interest. KOVID GARA is expected to be able to entertain, educate, shape children's character, KOVID GARA features are also designed to shape interests and talents in children so that in the future a generation with character and culture will be created. The culture in question is a culture of manners, the use of good and correct Indonesian language, to cultures such as arts and customs that will be included in KOVID GARA.  The method of service carried out is product development and conducting socialization experiments regarding this video comic. The output of this community service social project is a product that will be published on YouTube and given soft copies to teachers so that it can be used in learning. KOVID GARA's success target is seen from the number of initial episodes worked on, the number of impressions and the number of audience satisfaction, all of which meet the KPIs that have been set at the beginning.  So it can be concluded that KOVID GARA is feasible to be continued and developed as a form of community service social project.